Re: How to solve an implicit system?

*To*: mathgroup at smc.vnet.net*Subject*: [mg54566] Re: [mg54538] How to solve an implicit system?*From*: DrBob <drbob at bigfoot.com>*Date*: Wed, 23 Feb 2005 03:11:36 -0500 (EST)*References*: <200502220924.EAA10844@smc.vnet.net>*Reply-to*: drbob at bigfoot.com*Sender*: owner-wri-mathgroup at wolfram.com

The solutions are periodic functions (with period 1): Simplify[{y[t + 1] == y[t] + (y[t + 1] - y[t]) + (z[t + 1] - z[t]), z[t + 1] == z[t] + (y[t + 1] - y[t]) + (z[t + 1] - z[t])}] {z[t] == z[1 + t], y[t] == y[1 + t]} Bobby On Tue, 22 Feb 2005 04:24:32 -0500 (EST), bananalimone <bananalimone at libero.it> wrote: > I've to solve the following (simplificated) system: > > y[t+1]=y[t]+(y[t+1]-y[t])+(z[t+1]-z[t]) > z[t+1]=z[t]+(y[t+1]-y[t])+(z[t+1]-z[t]) > > I would like to choose the iterative way, but I don't know how to > start. Anyway any solution is accepted! > > Please help me. > > \bananalimone > > > > -- DrBob at bigfoot.com www.eclecticdreams.net

**References**:**How to solve an implicit system?***From:*bananalimone@libero.it (bananalimone)